The Path to Employment for the Most Disadvantaged People by Means of Inclusive Businesses - Lázaro Blanco, Emilio; Martínez Polo, Miguel Angel (Cuadernos de Trabajo Social, 2013)
In this article, we analyze how disabled-inclusive businesses (Spanish term: “Empresas de Inserción” or “EIS”) have become in the past few years, thanks to accumulated experience and the resulting methodological systemization, a very efficient tool for social and employment integration for those with the most difficulties in our society. From our perspective, disabled-inclusive businesses cannot be conceived of just as an end in themselves; so they can achieve their maximum potential, they must be integrated into what has been planned as a socio-employment integration itinerary, that is to say, an individual track adapted to the needs of each person experiencing social exclusion which goes through the steps of training, accompaniment, and access to work. People in the integration process within these businesses begin to experience the sense of full civic participation and a self-awareness as workers, that they are contributing just like anyone else with their taxes and deductions, and they move from a sense of receiving a subsidy to drawing a salary. We will also see how these businesses generate social benefits, building community cohesiveness between areas and people, while contributing to building a productive economy since they do not stop being organizations active in the usual marketplace of goods and services. Finally, we will highlight the public savings offered by the work of disabled-inclusive businesses, whose relatively modest investments achieve a return for the public sector: currently, more than 6,000 Euros per integrated job, in terms of Social Security, personal income tax, VAT, corporate taxes and other taxes.
Keywords: disabled-inclusive business; employment inclusion; social exclusion; employability